Engineering an Ecological Civilization Along Shanghai’s Main Waterfront and Coastline: Evaluating Ongoing Efforts to Construct an Urban Eco-Network - Den Hartog, H. (Frontiers in Environmental Science, 2021)
Recent ecological civilization policies make clear that China is willing to play a leading role in a sustainable green transition. But there are still discrepancies in definitions, appreciation and evaluation of ecological assets. This paper examines how Shanghai works on a sustainability transition, with a focus on its main urban waterfronts and coastline, in the context of an extremely high population concentration, world’s highest real estate values, and continuous urban development pressure. This paper will mobilize insights from the academic field of sustainability transitions to show how urban planning and design ambitions are translated into realities on the ground. In its latest Shanghai Master Plan (2017-2035), the city commits itself to set an example for other Chinese cities. Moreover, Shanghai’s city leaders want to inspire and push cities internationally to become more adaptable and resilient, both in the Global South and Global North. The spatially most radical action to realize this ambition is to create “a green and open eco-network" with 60% of Shanghai’s municipal territory to be used for ecological purposes, mostly wetlands. This paper will examine three urban planning and design projects that have key positions within this eco-network. On all three sites there are land-use conflicts, between urban development and ecological (re-)development. The first case is the recent transformation of no less than 120 kilometers of former industrial dominated waterfront along the Huangpu River, of which half was completed between 2016 and 2021. The second case, Nanhui Coastal Wetland Reserve with adjacent Lingang New City; and the third case, Chongming Eco-Island, started both around the millennium and had a 2020 planning horizon. After learning lessons from their previous sustainable innovation journeys these latter two projects entered a new phase as part of the eco-network. The paper concludes with seven practical recommendations aimed to reduce discrepancies between expectations and their implementation in practice: (1) use clear definitions; (2) co-create a shared vision for the future; (3) stop building on vulnerable locations; (4) create conditions of social learning; (5) supervision needs to go beyond planning boundaries; (6) step beyond an anthropocentric approach; and (7) foster a more experimental approach.